Clinical Features and Prognosis of Patients With Coronary Spasm–Induced Non–ST‐Segment Elevation Acute Coronary Syndrome. Issue 3 (8th May 2014) - Nakayama, Naoki; Kaikita, Koichi; Fukunaga, Takashi; Matsuzawa, Yasushi; Sato, Koji; Horio, Eiji; Yoshimura, Hiromi; Mizobe, Michio; Takashio, Seiji; Tsujita, Kenichi; Kojima, Sunao; Tayama, Shinji; et al.
Abstract : Background: The prevalence, clinical features, and long‐term outcome of patients with non–ST‐segment elevation acute coronary syndrome (NSTE ACS) associated with coronary spasm are not fully investigated. Methods and Results: This observational multicenter study enrolled 1601 consecutive patients with suspected NSTE‐ACS who underwent cardiac catheterization between January 2001 and December 2010. A culprit lesion was found in 1152 (72%) patients. In patients without a culprit lesion, the acetylcholine provocation test was performed in 221 patients and was positive in 175 patients. In the other patients, coronary spasm was verified in 145 patients during spontaneous attack. Spasm‐induced NSTE‐ACS was diagnosed in 320 (20%) patients. Multivariable analysis identified age <70 years (odds ratio [OR] 2.19, 95% CI 1.58 to 3.04), estimated glomerular filtration rate >60 mL/min per 1.73 m 2 (OR 1.72, 95% CI 1.16 to 2.56), and lack of hypertension (OR 2.55, 95% CI 1.90 to 3.41), dyslipidemia (OR 2.76, 95% CI 2.05 to 3.73), diabetes mellitus (OR 2.49, 95% CI 1.78 to 3.48), previous myocardial infarction (OR 5.37, 95% CI 2.89 to 10.0), and elevated cardiac biomarkers (OR 2.84, 95% CI 2.11 to 3.83) as significant correlates of spasm‐induced NSTE‐ACS ( P <0.01 for all variables). Transient ST‐segment elevation during spontaneous attack (variant angina) was observed in 119 patients with spasm‐induced NSTE‐ACS. Variant angina was more common in nondyslipidemic men among patients with spasm‐induced NSTE‐ACS. Conclusions: The study showed frequent involvement of coronary spasm in the pathogenesis of NSTE‐ACS. Variant angina was observed in one third of patients with spasm‐induced NSTE‐ACS. Coronary spasm should be considered even in patients with less coronary risk factors and nonobstructive coronary arteries.